Simulation of laser processing of materials - Афанасьєва, О. В.; Демиденко, Є. Є.; Бітюков, А. Ю. (My University, 2021)
Simulation of processes of laser processing of materials are considered in this work. Computer simulation is based on the application of the COMSOL Multiphysics package. Properties of a model of the passage of laser radiation through a block made of dielectric material are researched.
Keywords: laser processing